2022
DOI: 10.1002/cncy.22658
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of benign renal tumors on limited material

Abstract: Angiomyolipoma, papillary adenoma, oncocytoma, and clear cell papillary renal cell tumor are common benign renal tumors that may be encountered on biopsy material. The diagnostic criteria, limitations, and accuracy as well as specific sign out terminology are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…It is important to note that there are entities for which a definitive diagnosis can be made on both FNA and core biopsy material. Conversely, there are other entities for which a definitive diagnosis cannot be reached on either FNA or core biopsy material because it is not possible to entirely exclude other entities on the differential diagnosis based on biopsy material alone 44 . A systematic review reported a pooled positive predictive value of 99.8% and negative predictive value of 68.5% for RMB 14 …”
Section: Pathology: Fna and Core Biopsymentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that there are entities for which a definitive diagnosis can be made on both FNA and core biopsy material. Conversely, there are other entities for which a definitive diagnosis cannot be reached on either FNA or core biopsy material because it is not possible to entirely exclude other entities on the differential diagnosis based on biopsy material alone 44 . A systematic review reported a pooled positive predictive value of 99.8% and negative predictive value of 68.5% for RMB 14 …”
Section: Pathology: Fna and Core Biopsymentioning
confidence: 99%
“…Sufficient material on the cell block or core biopsy is important to properly assess the morphology and perform immunohistochemistry and/or special staining to establish an unequivocal diagnosis. 44,76,78 Caution is advised when the specimen is limited and ancillary studies are not definitive. Reporting oncocytic neoplasm, favor oncocytoma with a comment stating that RCC cannot be entirely ruled out is recommended under these circumstances.…”
Section: Oncocytomamentioning
confidence: 99%
See 1 more Smart Citation
“…Whether this diagnosis can be made on cytologic material (including both fine-needle aspiration and core-needle biopsy) remains controversial. 9,12,19 However, if a benign diagnosis can be made, the majority of patients opt for active surveillance. 8 The largest series to date demonstrated an ROM for the diagnosis of oncocytoma on fineneedle aspiration, core-needle biopsy, and immunohistochemistry of 2%.…”
Section: Risk Of Malignancymentioning
confidence: 99%
“…However, when given a benign, diagnosis most patients chose active surveillance rather than definitive therapy 8 . Consequently, the ability to give a reliable benign diagnosis is critical in biopsy interpretation 9 …”
Section: Cytologic Diagnosis Rom In Older Seriesa Rom In Recent Seriesbmentioning
confidence: 99%